Sharia Insurance: An Islamic-Based Financial Protection Solution - Muhamad Ibnu Hajar; Arista Fitri Diana; Lathifatul Aulia (Journal of Applied Statistics and Data Mining, 2025)
Background: In Indonesia, Sharia Financial Institutions continue to develop, including in addition to banking companies, such as Sharia Insurance Institutions, Sharia Capital Markets, Sharia Pawnshops, Sharia Financial Institution Pension Fund (DPLK), Sharia Cooperatives, Waqf Agencies, Amil Zakat Agencies, BMT (Baitu al-Mâl wa at-Tamwil) and others. Although sharia insurance continues to develop, public interest is still lacking. This is based on a lack of literacy and socialization related to sharia insurance. Objective: This article aims to review more deeply matters related to sharia insurance, such as its definition, law, history, development, types of contracts, principles, differences between sharia and conventional insurance, premiums, and sharia insurance claims. The goal is to improve public understanding and confidence in sharia insurance. Methods: The method used in this study is a literature review. Results: This study provides a comprehensive synthesis of existing literature related to sharia insurance. Although no new empirical data is presented, the discussion highlights key aspects to address the public's lack of understanding and interest in sharia insurance. Conclusion: The study is expected to help the public better understand sharia insurance so that they become more confident and willing to take out insurance. Further research could focus on evaluating the effectiveness of educational or socialization programs to increase public literacy and participation in sharia insurance.